Clinical practice guidelines for management of hyperglycaemia in adults with diabetic kidney disease. Issue 4 (26th January 2022) - Karalliedde, Janaka; Winocour, Peter; Chowdhury, Tahseen A.; De, Parijat; Frankel, Andrew H.; Montero, Rosa M.; Pokrajac, Ana; Banerjee, Debasish; Dasgupta, Indranil; Fogarty, Damian; Sharif, Adnan; Wahba, Mona; et al.
Abstract: A significant percentage of people with diabetes develop chronic kidney disease and diabetes is also a leading cause of end‐stage kidney disease (ESKD). The term diabetic kidney disease (DKD) includes both diabetic nephropathy (DN) and diabetes mellitus and chronic kidney disease (DM CKD). DKD is associated with high morbidity and mortality, which are predominantly related to cardiovascular disease. Hyperglycaemia is a modifiable risk factor for cardiovascular complications and progression of DKD. Recent clinical trials of people with DKD have demonstrated improvement in clinical outcomes with sodium glucose co‐transporter‐2 (SGLT‐2) inhibitors. SGLT‐2 inhibitors have significantly reduced progression of DKD and onset of ESKD and these reno‐protective effects are independent of glucose lowering. At the time of this update Canagliflozin and Dapagliflozin have been approved for delaying the progression of DKD. The Association of British Clinical Diabetologists (ABCD) and UK Kidney Association (UKKA) Diabetic Kidney Disease Clinical Speciality Group have undertaken a literature review and critical appraisal of the available evidence to inform clinical practice guidelines for management of hyperglycaemia in adults with DKD. This 2021 guidance is for the variety of clinicians who treat people with DKD, including GPs and specialists in diabetes, cardiology and nephrology.